Estratigrafía de Secuencias en rocas carbonáticas Pérmicas en El Pongo de Mainique e Integrada al subsuelo de la Sub Cuenca Camisea, Cusco – Perú - Pozo Calle, Eloy Gerardo (2017)
The Pongo de Mainique (bear house, in language Matsiguenga) is a landform generated by the Urubamba River across the eastern Andes, causing a cut that allows the observation of all stratigraphic units from Ordovician - Silurian to Tertiary, highlighting the presence of the Permian units producing gas and condensate from the Camisea area. Wonderful place and natural laboratory for the application of sequence stratigraphy methodology in order to better understand the geology in order to propose strategies for exploration and development of gas reservoirs of the subbasin of Camisea.This paper is a first approach with diagnoses based on observations, descriptions and interpretations of sedimentary processes and sequence stratigraphy, suggesting genetic sequences of third order of importance in the strategy of hydrocarbon exploration and development planning of reservoirs. The genetic sequences were defined based on the description of sedimentary facies, facies associations, interpretation of sedimentary environments and sub-environments and identification of stratigraphic surfaces.